2013
DOI: 10.1142/s0218810413720337
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Common Digital Nerve Compression Caused by a Lipoma Arising From the Flexor Tenosynovium

Abstract: Lipoma of the hand is a common lesion, but lipoma arising from the flexor tenosynovium is a very rare tumor that induces peripheral nerve disorders. Only four cases of synovial lesions that comprised mature fat at the wrist and imitated carpal tunnel syndrome have been described in the literature. We herein report an unusual case of a lipoma arising from the flexor tenosynovium at the level of the ring finger just proximal to the A1 pulley that was responsible for a sensory disturbance of the ring and middle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In both cases, removal of the lipoma resulted in recovery of bony erosion. Suginaka et al[ 12 ] reported a case of a male patient in his 60s who was diagnosed with a 4-cm lipoma in the flexor tenosynovium compressing the common digital nerve and leading to neurological symptoms. Gurich and Pappas[ 13 ] reported a lipoma of tendon sheath origin in the fourth extensor compartment of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, removal of the lipoma resulted in recovery of bony erosion. Suginaka et al[ 12 ] reported a case of a male patient in his 60s who was diagnosed with a 4-cm lipoma in the flexor tenosynovium compressing the common digital nerve and leading to neurological symptoms. Gurich and Pappas[ 13 ] reported a lipoma of tendon sheath origin in the fourth extensor compartment of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…First-line therapy of PS involve non-steroidal anti-inflammatory drugs that usually provide short-term pain relief. Patients can also try physical therapy with stretching exercises including external rotation, hip flexion, and adduction [12].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,8,9 Local causes like wrist fractures or soft tissue tumors have also been reported. 10,11 Muscular abnormalities are found mainly in manual workers. Those abnormalities concern three muscles: the palmaris longus, the flexor digitorum superficialis of index, and the lumbricals.…”
Section: Discussionmentioning
confidence: 99%